Taṭbīq Kitāb al-Ṣarf al-Muyassar bi al-Madkhal al-‘Ilmī bimarkaz Tarqiyyah al-Lugah al-‘Arabiyyah - Ulum, Moh.; Hasanah, Maidatul (Study Program of Arabic Language Teaching, 2023)
This development research aims to determine the process of preparing textbooks with a scientific approach, measuring the validity and effectiveness of using the book. The method used in this research is qualitative & quantitative research using Addie's approach; the researcher conducted a needs analysis and collected data related to preparing textbooks. Then this jar book was validated by experts & analyzed using the Likert Scale formula. Then a trial was carried out to prepare teaching materials with the pretest & post-test approach. Pretest & post-test results were analyzed using the t-test to measure its effectiveness. The results of the study show that textbooks are feasible to use. Based on the validity of the experts, This textbook gets a score of 87.2% from book experts, and gets a score of